The Effect of Display Polarity on Reading Speed and Reading Error Among Young Adults - Muhamad, Nurulain; Mokhtar, Nurliyana (Journal of Health Science and Medical Research, 2024)
Objective: The widespread adoption of digital devices has surged, particularly since the coronavirus disease 2019 (COVID-19) pandemic. Nearly everyone now owns devices like laptops, tablets, or smartphones, offering options for light mode (positive polarity) and dark mode (negative polarity) to suit individual preferences. This study examines how display polarity affects reading performance among young adults. Material and Methods: Thirty participants engaged in a 15-minute reading task on a laptop with randomly assigned display polarities, followed by a 15-minute break before repeating the task. Results: Reading speed, measured in words per minute (wpm), differed significantly between polarities, with negative polarity yielding higher speeds (136.27±25.58 wpm) compared to positive polarity (128.42±19.98 wpm), Z=-2.355, p-value<0.05. However, no significant polarity-related differences were found in reading errors, including mispronunciation (p-value=0.193) or omission (p-value=0.113). Conclusion: Negative polarity displays enhanced reading performance by increasing reading speed; while reading errors remained unaffected.